2022
DOI: 10.1186/s12891-022-05615-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessments and gait analysis for patients with Trimalleolar fractures in the early postoperative period

Abstract: Background Trimalleolar fracture is a common ankle fracture with serious complications and costly healthcare problem. Most studies used clinical assessments to evaluate the functional status of the patients. Although clinical assessments are valid, they are static and subjective. Dynamic, objective and precise evaluations such as gait analysis are needed. Ankle biomechanics studies on gait in patients with trimalleolar fractures are still rare. This study aimed to investigate the clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…A study of dynamic plantar pressure changes at 6 and 12 months after bilateral ankle fracture surgery showed that AFG patients had lower plantar pressure (peak and mean) and longer contact time than did CG patients and that AFG patients had significantly lower e-cadence and gait speed than did the control group. Similarly, (Fernández-Gorgojo et al, 2023), Zhu et al (2022) reported similar results in a study of 12 subjects after trimalleolar fracture; i.e., abnormal changes in plantar pressure were mainly manifested in the forefoot and hindfoot regions. Compared with those in the healthy control group, the patients in the symptomatic group had shorter step lengths, larger step widths, slower walking speeds, shorter single supports and obvious asymmetry in gait; these authors believe that these differences might be related to functional impairment of the anterior tibial and peroneal longus muscle ability.…”
Section: Ankle Fracturesupporting
confidence: 63%
“…A study of dynamic plantar pressure changes at 6 and 12 months after bilateral ankle fracture surgery showed that AFG patients had lower plantar pressure (peak and mean) and longer contact time than did CG patients and that AFG patients had significantly lower e-cadence and gait speed than did the control group. Similarly, (Fernández-Gorgojo et al, 2023), Zhu et al (2022) reported similar results in a study of 12 subjects after trimalleolar fracture; i.e., abnormal changes in plantar pressure were mainly manifested in the forefoot and hindfoot regions. Compared with those in the healthy control group, the patients in the symptomatic group had shorter step lengths, larger step widths, slower walking speeds, shorter single supports and obvious asymmetry in gait; these authors believe that these differences might be related to functional impairment of the anterior tibial and peroneal longus muscle ability.…”
Section: Ankle Fracturesupporting
confidence: 63%
“…Complementary to these functional scales, clinical parameters such as ankle dorsiflexion range of motion (ADF ROM), level of swelling, and muscle atrophy provide objective measures of clinical status at different stages of rehabilitation [18,26,27]. The recovery of these parameters after ankle surgery is critical and may play an important role in the full recovery of gait functionality [28] or balance [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advancements in technology have led to reliable, affordable, and compact sensors for gait analysis, enabling its application outside of a laboratory setting. Gait analysis has been applied in several sectors, including healthcare [2], security [3], and fitness [4] domains. According to the type of sensors involved and the methodologies chosen for assessing the gait, the available techniques can be classified into three main categories: image processing-based [5], floor sensors-based [6], and wearable sensors-based [7].…”
Section: Introductionmentioning
confidence: 99%